A Flexible Web‐Based Approach to Modeling Tandem Photocatalytic Devices. Issue 1 (20th December 2016) - Seger, Brian; Hansen, Ole; Vesborg, Peter C. K.
Abstract : There have been several works modeling the optimal band gaps for tandem photocatalytic water splitting devices under different assumptions. Due to the many parameters involved, it is impossible for the authors to consider every conceivable situation. In this work, we have developed a web‐based model (WBM) that allows users to input data such as photoabsorber diode parameters, catalytic losses, ionic losses, light concentration, etc. This program also adds a new parameter that allows one to balance the photon absorption distribution between both photoabsorbers in a tandem device (by thinning the top photoabsorber), thus allowing for a broader range of band gap combinations that can still provide highly efficient devices. While this does not change the overall maximum efficiency point, at certain band gap combinations balancing the photon absorption distribution between photoabsorbers can increase Solar to Hydrogen (STH) efficiency by up to 15% points. An additional feature of the WBM is that it allows users to upload data of a single photoelectrode, and then investigate the optimal matching photoabsorber band gap to maximize tandem device efficiency. This work analyzes some of the best previous experimental photoelectrodes, and quantitatively relates their performance to what would typically be expected via modeling programs. Abstract : This work describes a web‐based model for photoelectrochemical reactions. The program can do both theoretical modeling as well as take user‐generated experimental data and model performance based on this. This work uses previous best in class photoelectrochemical half‐cells to analyze optimal 2‐photoabsorber water splitting efficiencies.